Katalog Digital Multibahasa Sebagai Alat Promosi UMKM dan Desa Wisata Bahasa di Kelurahan Potrobangsan Kota Magelang - Simamora, Alex Johanes; Prasetyo, Andreas Yogi; Yudhanto, Wildan; Maulana, Muhamad Aji (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2025)
MSME players in Potrobangsan Village face obstacles in communicating with foreign consumers, especially in the use of foreign languages. To overcome this problem, a multilingual digital catalog has been developed that contains descriptions of MSME products in several languages. This catalog aims to facilitate communication between MSME actors and inter-national consumers, as well as increase the visibility and competitiveness of MSMEs in the global market. In addition, this digital catalog is also expected to contribute to the preservation of regional languages, such as Javanese, which are becoming endangered. The methods used include a preparatory stage in the form of field analysis, then a needs analysis stage, and continued with the stage of making a multi-language online catalog. The catalog development process involved training for MSME players, creating attractive and relevant product descriptions, and developing an online catalog platform. As a result, this catalog has succeeded in increasing sales and expanding the market reach of MSMEs in Potrobangsan Village.Keywords: MSME; multilingual digital catalog; potrobangsan Abstrak: Pelaku UMKM di Desa Potrobangsan menghadapi kendala dalam berkomunikasi dengan konsumen mancanegara, terutama dalam penggunaan bahasa asing. Untuk mengatasi masalah ini, telah dikembangkan katalog digital multibahasa yang memuat deskripsi produk UMKM dalam beberapa bahasa. Katalog ini bertujuan untuk memfasilitasi komunikasi antara pelaku UMKM dengan konsumen internasional, serta meningkatkan visibilitas dan daya saing UMKM di pasar global. Selain itu, katalog digital ini juga diharapkan dapat berkontribusi pada pelestarian bahasa daerah, seperti Bahasa Jawa, yang mulai terancam punah. Metode yang digunakan antara lain tahap persiapan berupa analisis lapangan, kemudian tahap analisis kebutuhan, dan dilanjut dengan tahap pembuatan katalog online multibahasa. Proses pengembangan katalog melibatkan pelatihan bagi pelaku UMKM, pembuatan deskripsi produk yang menarik dan relevan, serta penyusunan platform katalog daring. Hasilnya, katalog ini telah berhasil meningkatkan penjualan dan memperluas jangkauan pasar UMKM di Desa Potrobangsan.Kata kunci: UMKM; katalog digital multibahasa; potrobangsan.